2021
DOI: 10.1037/law0000299
|View full text |Cite
|
Sign up to set email alerts
|

Do structured risk assessments predict violent, any, and sexual offending better than unstructured judgment? An umbrella review.

Abstract: The funders had no role in the study design, data collection, data analysis, or manuscript composition. We thank Shanna Li and Julia Schillaci-Ventura for data entry and editing and Dr. Matthew Sigal for statistical assistance with the ggplot2 package in R. Jodi L. Viljoen designed the study, wrote the protocol, conducted analyses, and wrote the manuscript. Lee M. Vargen, Dana M. Cochrane, Melissa R. Jonnson, Ilvy Goossens, and Sanam Monjazeb extracted data from the studies, conducted analyses, and contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 77 publications
0
17
0
1
Order By: Relevance
“…In this sense, several studies and reviews pointed out the methodological limitations of the existing research (e.g., Dressel & Farid, 2018; Litwack, 2001; Mossman, 1994) and indicated that the accuracy of unstructured assessments might not be as limited as stated (e.g., de Vogel et al, 2004; Lin et al, 2020; Melton et al, 2018). For example, a recent umbrella review of systematic reviews comparing structured and unstructured risk assessment methods reported that “although research is generally consistent in reporting that risk assessment tools are superior to UCJ, studies used to support this statement showed serious problems in terms of risk for bias and lack of direct comparison” (Viljoen et al, 2021, p. 92). The authors showed, for example, that almost the entire state of research was conducted decades ago and nearly two thirds of the primary studies included in most reviews were published in the 1980s or earlier.…”
Section: Generations Of Risk Assessment Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, several studies and reviews pointed out the methodological limitations of the existing research (e.g., Dressel & Farid, 2018; Litwack, 2001; Mossman, 1994) and indicated that the accuracy of unstructured assessments might not be as limited as stated (e.g., de Vogel et al, 2004; Lin et al, 2020; Melton et al, 2018). For example, a recent umbrella review of systematic reviews comparing structured and unstructured risk assessment methods reported that “although research is generally consistent in reporting that risk assessment tools are superior to UCJ, studies used to support this statement showed serious problems in terms of risk for bias and lack of direct comparison” (Viljoen et al, 2021, p. 92). The authors showed, for example, that almost the entire state of research was conducted decades ago and nearly two thirds of the primary studies included in most reviews were published in the 1980s or earlier.…”
Section: Generations Of Risk Assessment Approachesmentioning
confidence: 99%
“…Several studies did not focus particularly on risk assessment instruments and did not provide direct head-to-head comparisons between ARAIs or SPJ tools and UCJs. Given these research desiderata, further empirical studies which directly compare unstructured with structured risk assessment methods are highly recommended (Viljoen et al, 2021).…”
Section: Ongoing Debate On Limited Accuracy Of Ucjsmentioning
confidence: 99%
“…For years, forensic psychology research has been concerned with demonstrating the reliability and predictive validity of violence risk assessment tools [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Currently, there are more than 200 violence risk assessment tools with a wide range of applications and varying levels of accuracy [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research pursuits of alternative strategies and theories to performing risk assessment must always occur in an ethically informed rational and empirical manner (Andrews et al, 2006). Although there is much evidence supporting the accuracy of actuarial prediction over unstructured clinical judgment (AEgisdóttir et al, 2006;grove et al, 2000;Harris et al, 2015), the quality of this evidence has some limitations due to research biases (Viljoen et al, 2021). There is also ongoing debate around the advantages and limitations of second versus third-generation approaches (Coid et al, 2009;Nicholls et al, 2016).…”
Section: Introductionmentioning
confidence: 99%